2022
DOI: 10.1186/s12902-022-01001-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the dietary inflammatory index with obesity and body fat in male adolescents

Abstract: Background Obesity and body composition may be affected by the pro-inflammatory and anti-inflammatory components of diets. The aim of this study was to investigate associations between the dietary inflammatory index (DII) and body fat percentage (BF%) in male adolescents. Methods This cross-sectional study was carried out on 535 adolescent boys in Tehran, Iran. Bio-impedance analyzer (BIA) scale was used to measure body mass index (BMI) and body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Bohlouli et al showed that adherence to an anti-inflammatory diet such as the Mediterranean diet improved fatigue severity in relapsing-remitting MS ( 57 ). Cross-sectional studies showed that the body composition and anthropometric measurements were directly associated with DII scores ( 58 , 59 ). There are evidence that high DII scores have been positively associated with an increased risk of obesity in non-obese individuals and also the prevalence of overweight and obesity ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bohlouli et al showed that adherence to an anti-inflammatory diet such as the Mediterranean diet improved fatigue severity in relapsing-remitting MS ( 57 ). Cross-sectional studies showed that the body composition and anthropometric measurements were directly associated with DII scores ( 58 , 59 ). There are evidence that high DII scores have been positively associated with an increased risk of obesity in non-obese individuals and also the prevalence of overweight and obesity ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics are presented as mean (standard deviation) or median (interquartile range) for continuous variables and proportional for categorical variables. We classified DII >0 as the pro-inflammatory diet group, and DII <0 as the anti-inflammatory diet group [18]. In addition, considering comparability across populations, we used the quartiles of DII in the total population for the segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a randomized controlled trial (RCT) study examining the metabolic level and inflammatory status of 81 participants indicated that an anti-inflammatory diet led to a significant decrease in body weight and visceral adipose tissue and improved the cardiometabolic and inflammatory status of the participants [ 91 ]. Moreover, a cross-sectional study on 535 adolescent boys found that adherence to a diet with a low inflammatory index score was related to a reduction in body fat percentage [ 92 ].…”
Section: Influence Of Anti-inflammatory Diet On Gut Microbiota Insuli...mentioning
confidence: 99%